The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1149/1.3261803
|View full text |Cite
|
Sign up to set email alerts
|

Computational Modeling of Bounding Conditions for Pit Size on Stainless Steel in Atmospheric Environments

Abstract: This paper presents analytic expressions for calculating bounding conditions for pitting under atmospheric conditions. These expressions allow the prediction of the maximum pit size that can develop under known atmospheric conditions by considering the factors that can control the inherent galvanic coupling between a circular pit under a thin electrolyte layer surrounded by a concentric cathodic area. Expressions are developed for the maximum cathodic current and the minimum anodic current required for pit sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 38 publications
1
119
0
Order By: Relevance
“…Ernst and Newman [49] reported that the critical concentration of metal cation C * was approximately 60 % of the saturation concentration, C s . The value of 60 % of saturation as an upper bound for the critical concentration has been observed for 316 L from previous work [52] on the experimental validation of the maximum pit size model [60]. Using the intercept for DC * instead of the DC s from Fig.…”
Section: Experimental Determination Of D M and C Satmentioning
confidence: 87%
See 1 more Smart Citation
“…Ernst and Newman [49] reported that the critical concentration of metal cation C * was approximately 60 % of the saturation concentration, C s . The value of 60 % of saturation as an upper bound for the critical concentration has been observed for 316 L from previous work [52] on the experimental validation of the maximum pit size model [60]. Using the intercept for DC * instead of the DC s from Fig.…”
Section: Experimental Determination Of D M and C Satmentioning
confidence: 87%
“…Hydrochloric acid was added to adjust the pH of the lithium chloride solutions to that of the ferric chloride solution of similar chloride concentration. Each electrochemical experiment started by applying +750 mV versus SCE potentiostatically for 5,10,15,20,30,45,60, or 120 min to grow one-dimensional pits of different depths. After each potentiostatic hold, the potential was scanned at a rate of 1 mV s −1 in the cathodic direction.…”
Section: Methodsmentioning
confidence: 99%
“…In this manner, salt load can control available anode-cathode area through electrolyte coverage and corrosion cell efficiency (volume and geometry); higher salt loads generally increase coverage and volume and tend towards thin, continuous films. Factors affecting efficiency include electrolyte resistance, which can reduce the effective cathode area, 20,21 along with the electrolyte path length for oxygen to reach the surface when oxygen reduction is the rate limiting step. 22,23 While the individual relationships of these factors with electrolyte geometry are generally understood under ideal conditions at the initial stage of corrosion, less is known regarding their combined influence or competition experienced as corrosion advances.…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45] Likewise, concepts crucial to passivation breakdown such as oxide film dissolution, film destabilization by halide complexation, localized corrosion cells (pits, crevices, thin films, or droplets), and solution acidification via metal ion hydrolysis all find a need for analysis by chemical stability diagrams. 43,[45][46][47][48] Some corrosion inhibitor technologies, which rely on the formation of a protective film via chemical storage, release, and subsequent chemical deposition, could benefit greatly from these types of analyses as well. For example, lead pipe water distribution systems are made safer via treatment with phosphate inhibitors.…”
Section: Extended Utility Of Chemical Stability Diagramsmentioning
confidence: 99%